The Effect of the Professionality of the State Civil Apparatus on the Achievement of Strategic Objectives - Rais Rofik, Muhammad Amien; Maulizar, Muhammad; Dwi Astuti, Christina (Green Publisher Indonesia, 2022)
This study aims to examine the effect of four dimensions of the SCA (Civil Servant) Professionality Index on public service quality and the achievement of strategic goals other than public service quality. The independent variables in this study are educational qualification, competency, performance, and discipline. Meanwhile, the dependent variables in this study are public service quality and the achievement of strategic goals other than public service quality. The population in this study is all of the work units in the State Civil Service Agency which are located throughout Indonesia from 2020 to 2021. The type of data used is secondary data, namely IP SCA calculation evaluation report and performance report. The analytical model used in this study is a multiple linear regression analysis using IBM Statistics 26. Based on the results of the analysis that has been carried out, it can be concluded that competence and performance have a positive effect on the quality of public services, while educational qualifications have a positive effect on the achievement of non-public-service-quality strategic goals. But, discipline does not affect the quality of public services and the achievement of non-public-service-quality strategic goals. This research implies that civil servants and government institutions must pay attention to educational qualifications, competence, and performance because these 3 things affect government performance.